Movable cable wrapping material and preparation method thereof
Through the blend crosslinking technology of random polyethylene-propylene-butene rubber and polyolefin resin, a thermoplastic elastomer is formed, which solves the problem that cable surfacing materials are susceptible to water at high voltages, and achieves high strength and low deformation And excellent electrical performance cable cover, suitable for DC insulation and low temperature softness requirements, and reduces preparation costs.
Patent Information
- Application Number
- CN202310737497.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2024-12-24
AI Technical Summary
Existing cable surfacing materials are susceptible to water at high voltages and lead to insulation damage, and are costly to prepare, and are difficult to meet the requirements of DC insulation and low temperature softness.
Random polyethylene-propylene-butene rubber (EPBR) is blended and cross-linked with polyolefin resin, and the thermoplastic elastomer (TPV) is formed through dynamic vulcanization, which is used for insulating sheath of metal cables, combining appropriate amounts of filling materials and vulcanization. to improve the strength, elasticity and processing properties of the material.
It realizes high-strength, low deformation, easy-to-process cable cover material, with excellent high-low temperature resistance and electrical properties, and is suitable as a movable DC insulated cable material, reducing preparation costs and avoiding "hydrophobia" The problem.
Smart Images

Figure CN119176989A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a cable sheath material, in particular to a movable cable sheath material based on hydrogenated random polybutadiene-isoprene rubber, and also to a preparation method thereof, belonging to the technical field of new synthetic rubber materials. Background Art
[0002] Common cable sheath materials in the prior art include polyvinyl chloride (PVC), polyethylene (PE), polyperfluoroethylene propylene (F46), chlorinated polyethylene (CPE), chlorosulfonated polyethylene (CSM), neoprene, silicone rubber, nylon and polyolefins. Polyethylene and cross-linked polyethylene have wide applications, large dosage, high resistivity, high breakdown field strength, good weather resistance and processability. They are currently the best electrical insulation materials and are mainly used as communication cables and high-voltage cable insulation and cable sheaths. However, they are only suitable for AC insulation, but not for DC insulation. At the same time, they are also "hydrophobic". Their breakdown is often related to the presence of water, forming "water branches" under high voltage, resulting in insulation damage. However, materials such as PVC, PE, F46, nylon, polyolefins, CPE, and CSM, even if filled with softeners, show rigid behavior that cannot be wound at low temperatures. Windability and softness are necessary conditions for movable cable materials.
[0003] As we all know, ethylene propylene diene monomer rubber (EPDM) is a non-polar polymer, belonging to hydrocarbon rubber, with unlimited filling capacity with rubber oil, and its softness can be adjusted arbitrarily. It has excellent heat resistance, weather resistance and chemical structure stability. Especially in terms of electrical properties, it has excellent high insulation resistivity characteristics, and is more suitable for the insulating material part of wires and cables. In the current market, there are many types of EPDM, but each has its own strengths. However, there are relatively few EPDM rubber brands that are more suitable for processing and extrusion in the wire and cable industry, and have relatively stable electrical properties.
[0004] In the prior art, some people choose EPDM with a Mooney viscosity of 22-23 (125°C), medium unsaturation and ethylene content of 65-70%, such as K2470L produced by Lanxess, and cable composites composed of stearic acid, zinc oxide, antioxidant, paraffin oil, high-temperature clay and talcum powder, coupling agent and diisopropylbenzene peroxide (DCP), which show good mixing, processing and physical properties. Similarly, in ("Application of EPDM Rubber and Ethylene-Butene Elastomer in Wire and Cable Insulation", Li Chunyang et al.), EPDM rubber and ethylene-butene elastomer are used together, with peroxide DCP as vulcanizing agent and TAIC as co-vulcanizing agent. A rubber with good dielectric insulation properties, physical and mechanical properties and processing performance is developed. The performance of the finished cable produced can fully meet the requirements of industry standards. The above technology uses peroxide as the vulcanization system. The preparation method of automobile rubber sealing strip disclosed in Chinese patent CN104592652A is to put EPDM, accelerator, antioxidant, carbon black, softening oil into an internal mixer at a mixing temperature of 100-110°C and a mixing time of 5-8min, then put in DCP and TAIC, and mix for 4-5min. After the mixed rubber is cooled, it is placed in a salt bath vulcanization bed for vulcanization under the vulcanization conditions of 230-250°C / 1.5-2min. The vulcanized rubber is pelletized and dried, and then the pellets are put into an extruder to extrude the product. The prepared pellets have the characteristic behavior of thermoplastic vulcanizate (Thermoplastic Vulcanizate) TPV, which belongs to dynamic vulcanization technology. The pellets prepared by vulcanizing the EPDM compound with peroxide can also be used for the sheath of cable materials. However, the production of pellets is prone to gelation, and the foreskin surface is rough, not bright, and has no matte defects. In ("EPDM in the Cable Industry and Modification", Xu Jianxiong et al.), EPDM with medium Mooney viscosity and medium ethylene content produced by DuPont DOW was publicly used to mix with zinc oxide, stearic acid, light calcium powder or (carbon black), accelerator, white oil and sulfur to compound white or black cable sheath. This technology requires drawing and microwave vulcanization, and the process is relatively complicated.
[0005] Although the existing EPDM has a large filling capacity, excellent weather resistance and heat resistance, it has low production efficiency during preparation, the conversion rate of monomers, especially propylene, is less than 48%, and ethylene cannot be fully converted at one time. The monomers need to be recovered and refined, resulting in a long process flow. The preparation of high Mooney viscosity EPDM also requires dry removal of volatiles, which has high preparation costs, resulting in high production costs. In addition, the presence of catalyst vanadium in the EPDM glue, which is difficult to remove, causes defects such as catalytic aging during use of the product.
[0006] In summary, only EPDM composite materials can meet the industry and use requirements for existing low-voltage movable cables. In the existing technology, there are three processes for cable materials: synthetic resin granular method, EPDM peroxide vulcanization and sulfur vulcanization. However, there has been no report on the low-cost preparation of soft movable towing cable sheath materials that can meet the requirements of high and low temperature resistance, weather resistance, aging resistance, easy processing and molding, bright surface and excellent electrical properties. Summary of the invention
[0007] In view of the defects of the prior art, the first object of the present invention is to provide a movable cable sheath material, which is a mixture of random polyethylene-propylene-butene rubber (EPBR) and polyolefin and filler material, and the polyolefin and EPBR are blended and cross-linked (dynamically vulcanized) under the action of peroxide, and granulated to obtain TPV (vulcanized thermoplastic elastomer). The granules are used as melt drawing and coating materials for metal cables, that is, insulating sheaths for metal cables, and have the advantages of easy processing, high strength, good elasticity, low deformation, easy injection molding, bright and plump surface of the product, resistance to high and low temperatures, aging resistance and excellent electrical properties.
[0008] The second object of the present invention is to provide a method for preparing a movable cable sheath, which is simple, low-cost, can be made using existing mature processes, and is easy to control and industrialize.
[0009] In order to achieve the above technical objectives, the present invention provides a removable cable sheath material, which comprises random polyethylene-propylene-butylene rubber and polyolefin resin;
[0010] The random polyethylene-propylene-butene rubber has a structure of Formula 1:
[0011]
[0012] Wherein, x, y, z, m, n, o, p and q are the degrees of polymerization, and x, y, z, m, n, o, p and q are all integers greater than or equal to 0; R is a branching unit; (n+o+p+q) / (x+y+z+m)=21~32; (y+z) / (x+m)=17.5~45; (y+m+n+o) / (x+p+z+q)=0.12~0.16.
[0013] The movable cable sheath material of the present invention mainly comprises EPBR components. EPBR has an alkyl main chain, has good compatibility and affinity with polyolefins, and does not produce phase separation. At the same time, the EPBR side chain contains double bonds, which can form a network-like macromolecule through oxide vulcanization. Under strong mixing, fine elastic rubber particles are formed and dispersed in the polyolefin (melt) continuous phase. The cross-linked network EPBR forms a dispersed phase of 1 to 5 microns, and locks the softened filling oil to form a soft elastic rubber phase, that is, the continuous phase polyolefin and the oil-filled cross-linked network EPBR dispersed phase form an "island" structure, which produces a stable physical contact point. The EPBR has an appropriate and evenly distributed side alkyl content, which reduces its crystallization and deformation, increases its elasticity, and has good comprehensive physical properties and processing properties when prepared with polyolefin resins and the like. However, the cable sheath prepared by single polyolefin resin has the defects of low rebound shrinkage, large compression deformation, poor low temperature resistance, and the existing EPDM composite insulation cable material has low melt index, poor rheological properties, rough or dull cable sheath surface, and the existing polyolefin is hydrophobic and cannot be used as DC cable.
[0014] As a preferred solution, the unsaturation degree of the random polyethylene-propylene-butene rubber according to the iodine value method is 3.0-4.5%.
[0015] As a preferred solution, the mass percentage of the side olefin polymerization unit in the front rubber of the random polyethylene-propylene-butene rubber is 20-33% (the side olefin polymerization unit is generated by the 1,2-addition unit of butadiene and the 3,4-addition unit of isoprene). The molar percentage of the side olefin polymerization unit in the random polyethylene-propylene-butene rubber is 3.5-4.5% (the polymerization unit of the side olefin chain is the double bond retained by the incomplete hydrogenation of the 1,2-addition unit of butadiene and the 3,4-addition unit of isoprene).
[0016] As a preferred embodiment, R is phenyl or alkylene.
[0017] As a preferred embodiment, the Mooney viscosity ML of the random polyethylene-propylene-butene rubber is 125 ℃=65~85, molecular weight distribution index M w / M n =2.0~2.5, crystallinity <3.
[0018] As a preferred solution, the removable cable sheath material comprises random polyethylene-propylene-butene rubber, polyolefin resin, rubber softening oil, inorganic filler, organic peroxide, crosslinking agent, sulfur and antioxidant. As a more preferred solution, the removable cable sheath material comprises the following components by mass: 100 parts of random polyethylene-propylene-butene rubber, 50-60 parts of polyolefin resin, 40-50 parts of rubber softening oil, 60-80 parts of inorganic filler, 0.70-0.85 parts of organic peroxide, 1.5-3 parts of crosslinking agent, 0.5-1.0 parts of sulfur, and 0.2-0.3 parts of antioxidant. In the removable cable sheath material of the present invention, the polyolefin resin is a continuous phase as the hard segment of the material, the rubber softening oil is used to fill the EPBR vulcanization crosslinking network, the inorganic filler is used as a reinforcing agent, the crosslinking agent is used to increase the density of the crosslinking network, and the organic peroxide and sulfur are vulcanizing agents for EPBR.
[0019] As a preferred solution, the polyolefin resin is injection blow molding grade polyethylene and / or polypropylene resin. The polyolefin resin is preferably at least one of injection blow molding grade polyethylene (PE) and polypropylene resin, etc., wherein polyethylene is most preferably, such as commercially available HDPE8085, DFDA7042, LDPE 1C7A and LD605. In addition, the amount of polyolefin resin needs to be controlled within an appropriate range. If the amount is too low, the TPV strength is low. If the amount of polyolefin resin is too high, the TPV hardness is large, the compression deformation is large, the resilience is low, and the contraction force of the composite cable is low. Generally speaking, polyolefin resin has high resistivity and breakdown field strength, good weather resistance, but polyolefin resin is only suitable for AC insulation, and is not suitable for DC insulation. At the same time, there is also "hydrophobia", and its breakdown is often related to the presence of water, forming "water branches" under high voltage, resulting in insulation damage. The present invention unexpectedly discovered that the use of EPBR and PE blended modified materials can overcome the disadvantages of using a single PE as an insulating sheath, which causes "hydrophobia" in the presence of water vapor and forms "water dendrites" under high voltage, leading to insulation damage. At the same time, it can also be further used as a low-voltage soft cable for DC insulation lines.
[0020] As a preferred solution, the rubber softening oil includes paraffin-based white oil. The rubber softening oil is selected from a softening oil known to technicians in the field, preferably a paraffin-based white oil, such as at least one of the commercially available 15#, 32#, 400N and 320# white oils. The amount of rubber softening oil is preferably controlled within a preferred range. If the amount of rubber softening oil is too low, the amount of inorganic filler in TPV increases, and the hardness increases; if the amount of rubber softening oil is too high, the hardness of TPV will decrease and the heat resistance will decrease.
[0021] As a preferred solution, the inorganic filler includes at least one of light calcium carbonate, calcined clay, talcum powder, and carbon black; more preferably, at least one of inexpensive light calcium carbonate, calcined clay, and talcum powder. The inorganic filler preferably has a particle size of 1 to 3 microns.
[0022] As a preferred solution, the organic peroxide includes at least one of di-tert-butyl peroxide isopropylbenzene (BIPB) and diisopropylbenzene peroxide (DCP); BIPB without odor is most preferred. Organic peroxide is mainly used for double bond crosslinking and vulcanization in EPBR molecules. If the dosage is too high, EPBR will produce gel, and TPV elongation and strength will decrease; if the dosage is too low, crosslinking is insufficient, strength is low, and resilience is poor.
[0023] As a preferred solution, the crosslinking agent includes at least one of TAIC and p-quinone dioxime. The amount of the crosslinking agent should not be too high, otherwise the crosslinking density will be too high or EPBR will produce gel, affecting the comprehensive physical properties of TPV. If the amount is too low, the crosslinking effect will be small.
[0024] The organic peroxide in the removable cable sheath of the present invention is the main substance that triggers the crosslinking of EPBR, which can cause the double bonds in EPBR to produce crosslinks. However, sulfur has a slow vulcanization speed for rubber with low unsaturation. A small amount of sulfur is added to TPV to make up for the loss of BIPB due to high temperature decomposition, which can further enhance the micro-crosslinking of EPBR. It is worth mentioning that if the amount of crosslinking initiator is too high, the crosslinking density of EPBR will be too large to produce gel; if the amount is too small, the crosslinking density is low and the strength is small.
[0025] As a preferred solution, the antioxidant includes at least one of a phenolic antioxidant and an amine antioxidant. The antioxidant can be an amine antioxidant or a phenolic antioxidant known to those skilled in the art for use in vulcanized rubber. EPBR has the function of resisting heat aging, so preferred phenolic antioxidants are 1076 or 1010, and preferred traditional amine antioxidants for use in vulcanized rubber are antioxidants such as antioxidant RD or antioxidant 4020.
[0026] As a preferred solution, the removable cable sheath material also contains 10 to 20 parts of colorant. The removable cable sheath material can be colored with commercially available inorganic or organic masterbatches known to those skilled in the art, such as carbon black, titanium dioxide, scarlet, ultramarine, and other colorants.
[0027] The present invention also provides a method for preparing a movable cable sheath material, wherein the preparation method comprises premixing materials including random polyethylene-propylene-butylene rubber and polyolefin resin, and then extruding and pelletizing the materials through a screw rod to obtain the movable cable sheath material.
[0028] As a preferred solution, the premixing temperature is 20-50°C and the premixing time is not less than 5 minutes.
[0029] As a preferred solution, the screw extrusion temperature is 160-170°C and the time is not less than 4 minutes.
[0030] The movable cable sheath material of the present invention is prepared by a dynamic vulcanization method: specifically, the materials are pre-mixed and then mixed, cross-linked, extruded, pelletized, and the like at high temperature by a twin-screw extruder.
[0031] The specific preparation method of the movable cable sheath material of the present invention is as follows: the material is put into a mixer for high-speed mixing, the temperature during the mixing process is 20-50°C, and the mixing time is not less than 5 minutes, and then the mixture is put into a twin-screw extruder, and mixed, vulcanized, cross-linked, and extruded at 160-170°C for not less than 4 minutes, and pelletized to obtain TPV pellets.
[0032] The movable cable sheath material of the present invention has a melt index MFR / 230°C of 5-8 g / min, 100% elongation strength>2.5 MPa, 300% elongation strength>3.5 MPa, tensile strength>7.0 MPa, elongation at break>500%, tear strength>50 KN / m, hardness 60-70A, deformation<60%. Volume resistivity (20°C / ohm.cm)>7.8×10 14 , dielectric constant>2.8, breakdown voltage (20℃) / (KV / mm)>26KV.
[0033] The movable cable sheath material (granules) of the present invention can be further prepared into movable cables by conventional methods: TPV granules are put into an extruder, sheared and melted at 180-190°C and extruded to a die head, and metal wires such as copper conductors or multiple groups of composite cable groups are passed through the die head hole and pulled at a uniform speed, at which time the surface of the conductor core or the composite cable group is evenly covered with a layer of TPV coating, cooled by cooling water for finalizing, and then wound and packaged. Single, double, three-strand or multi-strand cables can be prepared by extrusion according to different die heads.
[0034] The EPBR of the present invention can be prepared by the following method: after heating a polymerization solution system containing a structure regulator to a temperature required for initiating polymerization, continuously and evenly adding a mixed monomer including butadiene and isoprene, a branching agent and an initiator, initiating and carrying out a polymerization reaction to obtain a polymer glue, and the polymer glue is activated and subjected to a catalytic hydrogenation reaction to obtain the EPBR.
[0035] In the above method, the concentration of the structure regulator in the polymerization solution system is 100 to 220 mg / kg solvent. As a more preferred scheme, the structure regulator includes at least one of tetrahydrofurfuryl alcohol ethyl ether, ditetrahydrofurfuryl propane, tetrahydrofurfuryl alcohol butyl ether, and tetrahydrofurfuryl alcohol hexyl ether. The solvent is a conventional hydrocarbon solvent, such as cyclohexane. Selecting a suitable structure regulator and dosage can effectively regulate the 1,2 polymerization of butadiene and the 3,4 polymerization of isoprene, thereby effectively regulating the content of side alkyl and side olefin groups.
[0036] In the above method, the weight ratio of the isoprene to the butadiene is 0.15 to 0.20. The mass ratio of isoprene should not be too high or too low. If the amount of isoprene is too high, the unsaturation of the polyisoprene unit in the subsequent polymer hydrogenation will be too high, and the physical properties of the polymer will decrease, which is mainly reflected in the anti-aging and filling capacity of oil products and inorganic fillers. If the amount of isoprene is too low, the content of the introduced side olefin group is too low, which reduces the degree of vulcanization crosslinking and reduces the performance of the vulcanized rubber.
[0037] In the above method, the branching agent includes 1,3,5-hexatriene and / or divinylbenzene. When the branching agent is 1,3,5-hexatriene, it has a branching effect only when 1,2-addition occurs, and in the polymerization reaction system of the present invention, its 1,2-addition probability is 30-55%; 1,3,5-hexatriene cannot produce branched chains in the 1,4-addition, and only produces short chain segments of side olefins. In anionic polymerization, while the molecular chain grows, branching also occurs simultaneously, thereby increasing the weight average molecular weight of the polymer and widening the molecular weight distribution index of the polymer. As a preferred solution, the mass of the branching agent is 0.03-0.05% of the mass of the mixed monomer. It is not suitable to have too much branching agent, which is easy to produce macromolecular gel, which is disadvantageous. If the branching agent is not suitable to be too little, it is difficult to achieve the purpose of widening the molecular weight distribution.
[0038] In the above method, the mixed monomer, the branching agent and the initiator are respectively added to the polymerization solution system continuously and uniformly within 40 to 50 minutes. By controlling the uniform and continuous addition of the mixed monomer, the branching agent and the initiator, etc., the highly random copolymerization of the polymer can be effectively regulated, thereby adjusting the uniform distribution of the side vinyl groups in the EBDP and improving the vulcanization effect of the EBDP.
[0039] In the above method, the temperature required to initiate the polymerization reaction is 50-55°C, and the maximum temperature during the polymerization reaction does not exceed 75°C.
[0040] In the above method, the process of activation and catalytic hydrogenation reaction comprises the following steps: 1) adding alkyl lithium, activating for 10 to 15 minutes at a temperature of 65 to 80° C. and a hydrogen pressure of not less than 10 bar; 2) adding part of the promoter, activating for 10 to 15 minutes at a temperature of 65 to 80° C. and a hydrogen pressure of not less than 10 bar; 3) adding part of the main catalyst, hydrogenating for 40 to 60 minutes at a temperature of 70 to 120° C. and a hydrogen pressure of 13 to 16 bar; 4) adding part of the promoter, hydrogenating for 40 to 60 minutes at a temperature of 70 to 120° C. and a hydrogen pressure of 13 to 16 bar; 5) adding the remaining part of the main catalyst and the promoter at the same time, hydrogenating for 40 to 60 minutes at a temperature of 70 to 120° C. and a hydrogen pressure of 13 to 16 bar.
[0041] In the above method, the amount of alkyl lithium added is 12 to 18 times the total molar amount of the co-catalyst.
[0042] In the above method, the co-catalyst is dimethyl phthalate and / or methyl o-toluate.
[0043] In the above method, the amount of the co-catalyst added is 1 / 6 to 1 / 8 of the total molar amount of the main catalyst.
[0044] In the above method, the amount of the co-catalyst added in step 2), step 4) and step 5) accounts for 28-38%, 28-38% and 28-38% of the total molar amount of the co-catalyst respectively.
[0045] In the above method, the main catalyst is dicyclopentadiene titanium dichloride.
[0046] In the above method, the amount of the main catalyst used is 0.12-0.15 g / 100 g of polymer.
[0047] In the above method, the amount of the main catalyst added in step 3) and step 5) accounts for 60-80% and 20-40% of the total molar amount of the main catalyst respectively.
[0048] The present invention selects a dicyclopentadiene titanium dichloride catalyst system, which has a hydrogenation rate of more than 99% for double bonds in butadiene polymerization units, while for isoprene polymerization units, due to the steric hindrance effect of the side methyl groups and the methyl groups on the isopropylene double bonds in the molecules, the double bonds are not easy to be hydrogenated, and the double bonds on the main chain are easy to be hydrogenated with the double bonds on the isopropylene on the side chain. The goal of the present invention is to hydrogenate the double bonds on the main chain as much as possible, while retaining the double bonds on the side chains, which provide crosslinking points for subsequent application vulcanization, and the fewer the number of double bonds on the main chain, the more the number of double bonds on the side chains is relatively, which is beneficial to the anti-aging property of the vulcanized rubber, and the use of the dicyclopentadiene titanium dichloride catalyst system can achieve the expected selective hydrogenation effect. In addition, the main catalyst and the auxiliary catalyst are added to the hydrogenation system for catalytic hydrogenation in multiple times because the catalytic hydrogenation of the present invention belongs to active complex catalysis, the activity of the catalyst is relatively high at the initial stage, and it can complete 85% hydrogenation of the polybutadiene unit, but the activity decreases rapidly in the later stage. Therefore, the purpose of adding the catalyst in the later stage is to re-manufacture or establish a new catalytic active center, and hydrogenate the polybutadiene unit and the 1,4-addition polymerization unit of isoprene as much as possible, so as to retain the side isopropenyl functional group generated by the 3,4-addition of isoprene as much as possible.
[0049] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0050] The existing polyethylene used as insulating sheath for electric cables is only suitable for AC insulation, but not for DC insulation. It also has "hydrophobia" that forms "water branches", leading to insulation damage, and PE has poor aging resistance and low-temperature resistance. Polyolefin materials such as PVC and PE have high hardness and cannot be wound. They harden, have no elasticity and low shrinkage at low temperatures, resulting in small wrapping stress and poor windability of the prepared cables, making them unsuitable for movable cables.
[0051] The removable cable sheath material of the present invention is prepared from EPBR, polyethylene resin and filler, and has high strength, good elasticity, low deformation, easy injection molding, bright and plump product surface, good heat resistance, aging resistance and low temperature resistance, and is very suitable for use as a removable and retractable high and low temperature resistant soft cable. This is mainly due to the fact that PE and EPBR in the removable cable sheath material do not produce phase separation, that is, PE and EPBR both contain ethylene and show good compatibility. In addition, vulcanization crosslinking mainly occurs between EPBR molecules, forming EPBR into a network-like macromolecule, forming fine elastic rubber particles dispersed in polypropylene (melt) under strong mixing, dispersing PE into a continuous phase, and forming a crosslinked network of EPBR. ~5 micron dispersed phase, and the softening oil is locked to form a soft elastic rubber phase, that is, the continuous phase PP and the oil-filled cross-linked network EPBR phase form an "island" structure, which produces a stable physical contact. In addition, EPBR has a suitable and evenly distributed side group content, which reduces the crystallization and deformation of the material, increases the elasticity of the material, and gives the TPV cable insulation skin good comprehensive physical properties and processing properties.
[0052] The EPBR selected as the sheath material of the movable cable wire of the present invention has excellent electrical properties, improves the low breakdown voltage of the single PE material, and overcomes the disadvantage that the PE material is afraid of water.
[0053] The EPBR selected as the sheath material of the movable cable wire of the present invention retains the original behavior of PE and EPDM, improves the anti-aging performance and excellent comprehensive physical properties of PE, has the advantages of low manufacturing cost and the like.
[0054] The movable cable sheath material and the cable of the present invention can be manufactured by utilizing existing mature processes and are easy to control and industrialize.
[0055] The preparation method of the movable cable sheath material of the present invention adopts random polyethylene-propylene-butene ternary rubber (EPBR) and polyolefin and filler etc. to prepare the mixed vulcanization, and is used for the reelable high and low temperature resistant soft cable, avoiding the disadvantages of the existing PE, PVC and rubber containing a large number of unsaturated double bonds such as BR, SBR and NR etc. cables, such as poor low temperature resistance or poor aging resistance, and the existing SEBS / PP alloy has the defects of sticky surface after oil filling, poor heat resistance, large deformation and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 It is EPBR-1# original gel permeation color (GPC).
[0057] Figure 2 This is the H-NMR spectrum of EPBR-1# original gel.
[0058] Figure 3 This is the H NMR spectrum of EPBR-1# raw rubber
[0059] Figure 4 It is a EPBR / PE-5#-1TPV four-strand cable.
[0060] Figure 5 It is a EPBR / PE-5#-2TPV four-strand cable. DETAILED DESCRIPTION
[0061] The following examples are intended to further illustrate the present invention in detail and are not intended to limit the scope of protection of the claims of the present invention.
[0062] In the following examples, the number average molecular weight and molecular weight distribution index of the polymers were determined by gel permeation chromatography (GPC); 1 -NMR spectrum quantitatively determines the microstructure of the polymer; the mechanical properties of TPV are tested according to GB / T36089-2018 method; the Mooney viscosity of raw rubber is implemented according to GB1232 standard; the volume resistivity is tested according to GB / 31838.3 standard; the dielectric constant is tested according to GB1409-88 standard; the breakdown voltage is tested according to GB / T21222-2007 standard.
[0063] Example 1
[0064] Under nitrogen protection, 3000 mL of cyclohexane and 0.45 mL of 12.5% ETE cyclohexane solution were added to a 5L polymerization kettle, stirring was started and the material temperature was raised to 55°C. At this time, 0.5 mol / L NBL 5.5 mL (cyclohexane solution) and a mixed monomer consisting of 350 mL of butadiene, 45 mL of isoprene and 0.14 mL of divinylbenzene were added to the polymerization kettle respectively. The continuous addition time was 50 minutes. After the addition of the materials, polymerization was continued for 30 minutes, during which the polymerization temperature was maintained at no more than 75°C. The synthesized raw rubber (labeled as EPBR-1# raw rubber) was analyzed by gel permeation chromatography. Figure 1 , H NMR spectrum Figure 2 .
[0065] The glue liquid was pressed into the hydrogenation kettle with nitrogen, and 5 mL of 0.5 mol / L NBL was added, the temperature was raised to 70-80°C, and the mixture was stirred and activated for 10 min under 13 bar hydrogen pressure; then 4 mL of 0.02 mol / L cyclohexane solution of dimethyl phthalate and methyl o-toluate (cocatalyst, the molecular ratio of the two cocatalysts was 1:1) was added and activated for another 15 min, then 0.06 g of dicyclopentadiene titanium dichloride was added and stirred for 50 min under 15 bar hydrogen pressure, during which the hydrogenation temperature rose to 110°C, and after the kettle temperature dropped to 85°C, 3 mL of cocatalyst was added and stirred for 50 min under 14 bar hydrogen pressure; then 0.03 g of dicyclopentadiene titanium dichloride and 3 mL of cocatalyst were added to the hydrogenation kettle and stirred for 50 min under 14 bar hydrogen pressure.
[0066] Finally, the hydrogenated rubber solution was terminated with water, condensed, dehydrated and dried to obtain 251 g of granular EPBR-1# raw rubber, which was labeled as EPBR-1#. Its behavior characteristics are shown in Table 1. The nuclear magnetic hydrogen spectrum of EPBR-1# raw rubber is shown in Figure 3 .
[0067] Example 2
[0068] The relevant process conditions of Example 1 remain unchanged, except that 0.5 mL of 12.5% ETE cyclohexane solution and 0.14 mL of divinylbenzene are added. The total amount of dicyclopentadiene titanium dichloride used as the main catalyst for the hydrogenation unit is 0.12 g (of which the first addition amount is 0.07 g), the total amount of the co-catalyst is 12 mL (of which each first addition amount is 5 mL), and the total hydrogenation reaction time is 150 min.
[0069] The raw rubber obtained was calibrated as EPBR-2#, and its behavioral characteristics are shown in Table 1.
[0070] Example 3
[0071] The relevant process conditions of Example 2 were kept unchanged, except that 0.52 mL of 12.5% ETE cyclohexane solution and 47 mL of isoprene were added.
[0072] The raw rubber obtained was calibrated as EPBR-3#, and its behavioral characteristics are shown in Table 1.
[0073] Example 4
[0074] The relevant process conditions of Example 1 were kept unchanged, except that 0.56 mL of 12.5% ETE cyclohexane solution, 4.8 mL of 0.5 mol / L NBL, and 52 mL of isoprene were added.
[0075] The raw rubber obtained was calibrated as EPBR-4#, and its behavioral characteristics are shown in Table 1.
[0076] Example 5
[0077] The relevant process conditions of Example 1 were kept unchanged, except that 0.60 mL of 12.5% ETE cyclohexane solution, 4.5 mL of 0.5 mol / L NBL, and 58 mL of isoprene were added.
[0078] The raw rubber obtained was calibrated as EPBR-5#, and its behavior characteristics are shown in Table 1.
[0079] Example 6 (Comparative Example)
[0080] The relevant process conditions of Example 2 remain unchanged, except that the main and auxiliary catalysts are added to the hydrogenation kettle at one time in the hydrogenation section.
[0081] The raw rubber obtained was calibrated as EPBR-6#, and its behavioral characteristics are shown in Table 1.
[0082] Example 7 (Comparative Example)
[0083] The relevant process conditions of Example 2 were kept unchanged, except that 0.8 mL of ETE with a mass fraction of 12.5% and 6.5 mL of NBL with a mass fraction of 0.5 mol / L for polymerization were added.
[0084] The Mooney viscosity of the raw rubber was obtained. 1+4 ) is 56, the side ethyl content is 38%, and EPBR has self-adhesive blocks, which is not suitable for mixing with polyethylene pellets and twin-screw vulcanization and extrusion granulation.
[0085] Table 1 Analysis of polymer characteristics in the examples
[0086]
[0087] Example 8
[0088] EPBR / PE-TPV pellet preparation:
[0089] EPBR-1#, EPBR-2#, EPBR-3#, EPBR-4#, EPBR-5#, EPBR-6# in Table 1 and commercially available EPDM 3110 produced by Mitsui Chemicals and EPDM4770R raw rubber produced by DOW Chemical Company were mixed according to the formula of TPV in the present invention, mixed at room temperature for 6 minutes, and then mixed, vulcanized and cross-linked, extruded and pelletized in a twin-screw extruder at 170° C. for a residence time of 4 minutes to obtain EPBR / PE-TPV pellets.
[0090] The formula of each sample is shown in Table 2, and the physical properties of EPBR / PE-TPV are shown in Table 3.
[0091] Table 2 EPBR / PE-TPV formula (mass fraction)
[0092]
[0093] Note: Antioxidant 4020 and antioxidant 1010 are both 0.25 parts, and colorant carbon black 330 is 15 parts.
[0094] EPBR5#-2 represents a comparative sample with too high a crosslinking agent dosage.
[0095] Table 3 EPBR / PE-TPV physical properties
[0096]
[0097]
[0098] It can be seen from Table 3 that the TPV made of EPBR and PE of the present invention exhibits excellent comprehensive physical properties. However, the unsaturation degree is too high, and the anti-aging performance is poor; the amount of crosslinking agent is too high, and the rheological properties, processing properties and comprehensive physical properties deteriorate.
[0099] Example 9
[0100] EPBR / PE-TPV is used in the preparation of single strands
[0101] TPV and polyethylene granules LDPE 1C7A and PVC powder prepared by EPBR-1#, EPBR-2#, EPBR-3#, EPBR-4#, EPBR-5#-1, EPBR-5#-2, EPBR-6#, EPDM 3110, and EPDM4770R were placed in a single screw extruder to melt and squeeze into the side inlet of the die head, and a single multi-strand thin copper wire was inserted through the center hole of the die head, and then the single multi-strand thin copper wire was pulled at a uniform speed, and the copper wire could be covered with a uniform rubber and plastic surface layer, and a single strand was obtained after cooling and shaping. Among them, the injection molding temperature of TPV and LDPE 1C7A is 165-175℃, and the injection molding temperature of PVC filled with 40% dibutyl phthalate plasticizer is 230-240℃. The properties of various single strands are shown in Table 4.
[0102] Table 4 Performance of TPV, PE and PVC single strands
[0103]
[0104] As can be seen from Table 4, TPV exhibits excellent electrical properties and low-temperature resistance. However, when a small amount of gel appears in the TPV rubber molecule and the melt index (MFR) decreases, the curing temperature rises, the windability decreases, and the mobility is inconvenient. In addition, PE has a low breakdown voltage and PVC has poor low-temperature resistance.
[0105] Example 10
[0106] TPV for multi-strand cable preparation
[0107] The TPV pellets prepared from EPBR-5#-1 and EPBR-5#-2 were respectively used to make four-strand cables according to the preparation process and method of EPBR / PE-TPV single-strand cable in Example 1. The die drawing process and cable appearance in the process were shown in Figure 1. Figure 5 and Figure 5 The results showed that the surface of the EPBR / PE-5#-1TPV four-strand cable was smooth and matte, while the surface of the EPBR / PE-5#-2TPV four-strand cable containing a small amount of gel had slight flaws and no matte.
Claims
1. A removable cable sheath material, characterized in that: Contains random polyethylene-propylene-butene rubber and polyolefin resin; The random polyethylene-propylene-butene rubber has a structure of Formula 1: in, x, y, z, m, n, o, p and q are the degrees of polymerization, and x, y, z, m, n, o, p and q are all integers greater than or equal to 0; R is a branching unit; (n+o+p+q) / (x+y+z+m)=21~32; (y+z) / (x+m)=17.5-45; (y+m+n+o) / (x+p+z+q)=0.12~0.
16.
2. The removable cable sheath material according to claim 1, characterized in that: The unsaturation degree of the random polyethylene-propylene-butene rubber according to iodine value method is 3.0-4.5%.
3. The movable cable sheath material according to claim 1, characterized in that: R is a phenyl group or an alkylene group.
4. The movable cable sheath material according to claim 1, characterized in that: The Mooney viscosity ML of the random polyethylene-propylene-butene rubber 125 ℃=65~85, molecular weight distribution index M w / M n =2.0~2.5, crystallinity <3.
5. A movable cable sheath material according to any one of claims 1 to 4, characterized in that: It contains random polyethylene-propylene-butene rubber, polyolefin resin, rubber softening oil, inorganic filler, organic peroxide, crosslinking agent, sulfur and antioxidant.
6. The movable cable sheath material according to claim 5, characterized in that: The invention comprises the following components in parts by weight: 100 parts of random polyethylene-propylene-butene rubber, 50-60 parts of polyolefin resin, 40-50 parts of rubber softening oil, 60-80 parts of inorganic filler, 0.70-0.85 parts of organic peroxide, 1.5-3 parts of cross-linking agent, 0.5-1.0 parts of sulfur and 0.2-0.3 parts of antioxidant.
7. The movable cable sheath material according to claim 6, characterized in that: The polyolefin resin is injection blow molding grade polyethylene and / or polypropylene resin; The rubber softening oil includes paraffin-based white oil; The inorganic filler includes at least one of light calcium carbonate, calcined clay, talcum powder and carbon black; The organic peroxide includes at least one of di-tert-butyl cumene peroxide and dicumyl peroxide; The cross-linking agent includes at least one of TAIC and quinone dioxime; The antioxidant includes at least one of a phenolic antioxidant and an amine antioxidant.
8. The movable cable sheath material according to claim 5, characterized in that: Contains 10 to 20 parts of colorant.
9. The method for preparing a movable cable sheath material according to claim 5, characterized in that: The material including random polyethylene-propylene-butene rubber and polyolefin resin is pre-mixed, and then extruded and pelletized by a screw to obtain the product.
10. The method for preparing a movable cable sheath material according to claim 9, characterized in that: The premixing temperature is 20-50° C. and the premixing time is not less than 5 minutes.
11. The method for preparing a movable cable sheath material according to claim 9, characterized in that: The temperature of the screw extrusion is 160-170° C., and the time is not less than 4 minutes.
Citation Information
Patent Citations
Polyolefine sheathing compound for coaxial cable and preparation method thereof
CN102153812A
Cross-linking agent masterbatch used in dynamic sulfidation preparation of thermoplastic rubber and its prepared thermoplastic rubber
CN102352070A
Wide-distribution polybutadiene-isoprene rubber and preparation method thereof
CN112210040A
Process for preparing thermoplastic vulcanizates
CN1362977A
Soft polyolefin resin composition for power cables with excellent insulation characteristics and article molded therefrom
EP4148087A1
